The Analysis of Field Strains Isolated From Food, Animal and Clinical Sources Uncovers Natural Mutations in Listeria monocytogenes Nisin Resistance Genes - Wambui, Joseph; Eshwar, Athmanya K.; Aalto-Araneda, Mariella; Pöntinen, Anna; Stevens, Marc J. A.; Njage, Patrick M. K.; Tasara, Taurai (Frontiers in Microbiology, 2020)
Nisin is a commonly used bacteriocin for controlling spoilage and pathogenic bacteria in food products. Strains possessing high natural nisin resistance that reduce the potency of this bacteriocin against Listeria monocytogenes have been described. Our study sought to gather more insights into nisin resistance mechanisms in natural L. monocytogenes populations by examining a collection of 356 field strains that were isolated from different foods, food production environments, animals and human infections. A growth curve analysis-based approach was used to access nisin inhibition levels and assign the L. monocytogenes strains into three nisin response phenotypic categories; resistant (66%), intermediate (26%) and sensitive (8%). Using this categorization isolation source, serotype, genetic lineage, clonal complex (CC) and strain-dependent natural variation in nisin phenotypic resistance among L. monocytogenes field strains was revealed. The sequencing and comparison of known nisin response genes in a selection of high nisin resistance and sensitivity strains enabled the identification of different natural mutations that associated with increased nisin resistance and sensitivity in this bacterium. High nisin resistance was detected in strains harboring RsbU G77S and PBPB3 V240F amino acid substitution mutations, which also showed increased detergent stress resistance as well as increased virulence in a zebra fish infection model. On the other hand, high natural nisin sensitivity was detected among strains with mutations in sigB, vir and dlt operons that also showed increased lysozyme sensitivity and lower virulence. Overall, our study identified naturally selected mutations were identified involving pbpB3 (lm0441) as well as sigB, vir and dlt operon genes that contribute to intrinsic nisin resistance in L. monocytogenes field strains recovered from various food and human associated sources. The identification and validation of these natural occurring mutations in nisin response genes showed that combining growth parameter-based phenotypic analysis and targeted gene sequencing is an effective approach that can be useful for identifying novel nisin response genes among L. monocytogenes field strains.